2022
DOI: 10.1038/s41746-022-00649-y
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for real-time aggregated prediction of hospital admission for emergency patients

Abstract: Machine learning for hospital operations is under-studied. We present a prediction pipeline that uses live electronic health-records for patients in a UK teaching hospital’s emergency department (ED) to generate short-term, probabilistic forecasts of emergency admissions. A set of XGBoost classifiers applied to 109,465 ED visits yielded AUROCs from 0.82 to 0.90 depending on elapsed visit-time at the point of prediction. Patient-level probabilities of admission were aggregated to forecast the number of admissio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Similarly, after documenting the clinical history in an electronic health record (perhaps assisted by an AI scribe), AI tools could extract key features using natural language processing and with other parameters such as physiological observations and biomarkers, can support clinicians by generating a differential diagnosis, ensuring that critical diagnoses are considered, and identifying patients at higher risk of deteriorating [ 10 , 11 ]. At the hospital level, routine clinical data collected from a patient's arrival at the emergency department could be used to predict the patient's risk of needing admission, assisting with patient flow and service planning [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, after documenting the clinical history in an electronic health record (perhaps assisted by an AI scribe), AI tools could extract key features using natural language processing and with other parameters such as physiological observations and biomarkers, can support clinicians by generating a differential diagnosis, ensuring that critical diagnoses are considered, and identifying patients at higher risk of deteriorating [ 10 , 11 ]. At the hospital level, routine clinical data collected from a patient's arrival at the emergency department could be used to predict the patient's risk of needing admission, assisting with patient flow and service planning [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to classical statistical methods such as regression, machine learning methods have attracted much attention from medical researcher due to their simplicity and sometimes more accurate predictions. Recently, many studies have compared machine learning methods in survival analysis [6,9]. Machine learning techniques as non-parametric and less complex are good alternatives to statistical methods.…”
Section: Survival Machine Learning Analysismentioning
confidence: 99%
“…In this context, machine learning (ML), an application of artificial intelligence, is a promising and feasible tool to be used on large scale to identify these population subgroups. Some previous studies have demonstrated that ML models can predict the demand for urgent and emergency services 10,11 . Besides, a systematic review showed that ML could accurately predict the triage of patients entering emergency care 12 .…”
Section: Introductionmentioning
confidence: 99%